Cultivation and molecular characterization of complete genome sequences of M. pneumoniae isolated in Russia - Matsvay A.D.; Bezrukov V.M.; Nikolaeva P.A.; Stetsenko I.F.; Nurmukanova V.A.; Dikaya G.S.; Gordukova M.A.; Galeeva E.V.; Shipulin G.A. (Клиническая микробиология и антимикробная химиотерапия)
Objective.